From L1 Thinking to L2 Text: Exploring AI-Mediated Translanguaging in University EFL Writing Tasks - Nur Ifadloh; Busayo Oluwabukola Alao; Eka Pujiastuti (CV. Akademi Merdeka, 2026)
The increasing availability of artificial intelligence (AI) tools has reshaped how university students engage in academic writing, particularly in English as a Foreign Language (EFL) context where multilingual resources play a central role. This qualitative study explores how EFL students use AI tools to mediate translanguaging practices during academic writing tasks and how they interpret AI’s role in moving from L1-based thinking to L2 written production. Drawing on think-aloud protocols, reflective writing journals, writing artifacts, and semi-structured interviews, the study examines writing as a process-oriented and mediated activity. The findings show that students strategically employ AI to externalize ideas, negotiate meaning, and refine language while maintaining agency and authorship through critical evaluation and revision of AI-generated text. AI tools were perceived not only as linguistic support but also as cognitive and emotional scaffolding that reduced writing anxiety and facilitated engagement with complex academic tasks. By foregrounding students’ practices and interpretations, this study contributes to growing discussions on AI, translanguaging, and writing pedagogy, highlighting the need for process-oriented and reflective approaches to AI use in EFL writing instruction.